Orientação técnica para coordenadores pedagógicos: marcas da atuação de seus formadores - Lemos, Michael de Oliveira (2021)
Starting from questionings from a researcher who is an Educator from Public Elementary Education system of the State of São Paulo about technical orientation from which the coordinating teachers are part of, this study has as a main objective to Understand how the Pedagogical Coordinating teachers perceive the Technical orientation which come from the Pedagogical Core of a teaching School District. From the main objective, were unveiled the following specific main objectives: To identify how the formation through Technical Orientation made by the School District is received by the Pedagogical coordinating teacher, in the perception of them, identify how the Pedagogical Coordinating teachers cognize themselves starting from the Technical orientation and learn, from the testimonials of the Pedagogical coordinating teachers, possible suggestions to the School District in what refers to this Technical Orientation. The theoretical picture was constituted from contributions of Imbernón (in 2010), Zeichner (in 1993), Almeida (in 2015), Placco and Souza (in 2015b), Souza e Placco (2017), Silva (2019) e Pessoa (2015) among others. In which regards to the mothodological procedures, the qualitative research was the basis for the research instrument having André (2017 and Lüdke (2018) and André (2018) as a reference. This study counted with two sources which produced all the information: A reflexive interview and a Questionnaire, and they had as theoretical basis: ALMEIDA, PRANDINI and SZYMANSKI (2018), SZYMANSKI (2000) and questionnaire MIELZYNSKA (1989). The analysis results point out to the importance of Technical Orientation to the Pedagogical coordinating teachers. According to the subjects, they offer subsidy for the shaping of teachers’ training at schools, presenting the necessary theoretical grounds to the Pedagogical coordinating teachers, informing them about the necessities of the Education Bureau of the State of São Paulo, nevertheless, the results also point to the necessity of those guidelines being developed with more frequency, and that those structures to be closer to the reality experienced, to priviledge the academic training and not only the information and may the cascading development provided be reflected in all different instances they may reach